Water Quality Management in an Integrated Water Supply System - Minson, D.; Anwar, Faisal (2015)
The advancements to drinking water quality have been the number one factor in improving public health in the world. Perth’s surface water scheme has unique problems associated with its drinking water supply. Many of the Water Corporation’s sites use solely chlorine as their disinfection barrier to pathogen contamination as opposed to a full water treatment facility. In this research, the application of the Hazard Analysis and Critical Control Points (HACCP) system to Perth’s surface water scheme identifies issues, the causes and suggests improvements to maintain and improve compliancy. Canning Dam, a Water Corporation controlled site, was chosen as a case study site to apply the HACCP system for best practice. The results revealed that the performance of Canning Dam is not fully compliant with Australian Drinking Water Guidelines and it suggests that there is a need to improve the operation and management processes.